Introduction BASED INTERNET OF THINGS (IOT) SYSTEM IN SMA NEGRI 1 BRBEBES: INTRODUCTION TO ARDUINO-BASED INTERNET OF THINGS (IOT) SYSTEM IN SMA NEGRI 1 BRBEBES - ria indah fitra, M.Kom, ria; Firmansyah, Hasbi; Prasetyo Tulodo, Rizki (Universitas Pancasakti Tegal, 2023)
The introduction of the Arduino-based Internet Of Things (IOT) system at Brebes 1 Public High School helped the students there to develop the system. We are here to introduce students to how Arduino functions in today's modern era. Apart from the function, we also introduce how Arduino works and how to operate Arduino in a school environment. As an example that can be used by Arduino in the school environment is attendance by detecting faces or you can use the retina of the eye. There are many examples that can be taken from case studies on the use of Arduino which can be applied to the Brebes 1 Public High School school environment. The introduction of Arduino has many benefits for students at the school, because students can have many ideas that can be developed to make their school more modern or they can also make works which will then be published to introduce their school to the wider community. . Students can have a lot of ideas that they will develop and also because the equipment used in making the Arduino system is very affordable. Apart from the affordable price, Arduino is also not difficult to find equipment, because there are lots of Arduino equipment that are widely sold, both offline in computer stores or even online, which are sold freely.